Symbolic Capital and Muamalah Ethics in Government Vehicle Lease-Purchase Contracts - Afriyanti, Afriyanti; Fitri, Radia; Ruswandi, Ruswandi (El-Rusyd, 2026)
This study aims to analyze the practice of hire purchase for official vehicles by local governments from the perspective of Islamic commercial law (fiqh muamalah) and to examine its social impacts. The hire purchase system is a contemporary practice not recognized in classical Islamic jurisprudence, which only identifies separate contracts of ijarah (leasing) and bai’ (sale). In practice, government employees are treated as lessees until the final payment is made, after which ownership of the vehicle is transferred. This research employs a library-based approach using inductive, deductive, and comparative methods. The findings indicate that combining ijarah and bai’ contracts into a single agreement contradicts Islamic legal principles due to ambiguities in rights and obligations. Although similar to al-Ijarah al-Muntahiya bit-Tamlik, the current practice violates the structural requirement of separating contracts. Socially, this mechanism generates jealousy, bureaucratic inequality, and decreased public trust in the fairness of public service facilities. The study recommends restructuring the mechanism to align with Islamic legal principles and social justice values. Future researchers are encouraged to explore alternative Sharia-compliant models for state asset procurement that emphasize transparency, equity, and social acceptance, particularly within the context of public bureaucracy in Indonesia.